2017
DOI: 10.1017/s000711451700068x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels during pregnancy and associations with birth weight and body composition of the newborn: a longitudinal multiethnic population-based study

Abstract: We investigated associations between serum 25-hydroxyvitamin D (25(OH)D) in pregnancy and birth weight and other neonatal anthropometric measures. The present study was a population-based, multiethnic cohort study of 719 pregnant women (59 % ethnic minorities) in Oslo, Norway, delivering a singleton neonate at term and with birth weight measurements. In a representative sample, anthropometric measurements were taken. Maternal 25(OH)D was measured at gestational weeks 15 and 28. Women with 25(OH)D <37 nmol/l we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
1
39
1
Order By: Relevance
“…Multiple causes might explain the inconsistent findings, such as difference in birth period (1981-2002 v. 2010-2012), possible lifestyle changes between 1981 and 2012, sample selection (representative sample v. healthy women), 25(OH)D concentrations (27•2 (SD 18•3) v. 47•0 (SD 21•7) nmol/l) and methodological differences (DBS v. cord blood; adjustment for different confounders; residual confounding). In regard to Ponderal Index, no associations were found in the studies by Eggemoen et al and Gernand et al (8,43) . These discrepancies might be owing to different study designs, analytic methods and lack of power, but may also relate to the relative difficulty of measuring the crown-heel length of newborns.…”
Section: Birth Weight and Ponderal Indexmentioning
confidence: 84%
See 1 more Smart Citation
“…Multiple causes might explain the inconsistent findings, such as difference in birth period (1981-2002 v. 2010-2012), possible lifestyle changes between 1981 and 2012, sample selection (representative sample v. healthy women), 25(OH)D concentrations (27•2 (SD 18•3) v. 47•0 (SD 21•7) nmol/l) and methodological differences (DBS v. cord blood; adjustment for different confounders; residual confounding). In regard to Ponderal Index, no associations were found in the studies by Eggemoen et al and Gernand et al (8,43) . These discrepancies might be owing to different study designs, analytic methods and lack of power, but may also relate to the relative difficulty of measuring the crown-heel length of newborns.…”
Section: Birth Weight and Ponderal Indexmentioning
confidence: 84%
“…However, contrary to our findings, as well as to those of Zhu et al and Gernand et al, Shor et al and Eggemoen et al did not find an association between maternal vitamin D and birth weight. However, in these two latter studies, analyses were limited to using linear models (8,21,42,43) . Furthermore, another Danish study (44) found a U-shaped association between cord 25(OH)D and birth weight.…”
Section: Birth Weight and Ponderal Indexmentioning
confidence: 99%
“…There was no significant effect on growth parameters of the infant even if the mother showed vitamin D insufficiency/deficiency (Table 4). 9,10,11 . It is clear that there is lack of consensus and this conflicting evidence could be due to variations of study designs, timing of vitamin D testing during pregnancy, cut-off point of vitamin D deficiency, ethnicity and genetic variation of the study population.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable number of studies have shown that there is a link between maternal calcium and vitamin D status and fetal growth 1,8 . However, some studies have failed to demonstrate a relationship between vitamin D and neonatal growth parameters 9,10,11 . Reasons for such mixed results could be variations in study design, ethnicity and laboratory methods used.…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D deficiency of low birth weight might be the subsequent effect of maternal vitamin D deficiency. Many studies concluded that maternal vitamin D insufficiency is independently associated with low birth weight [21][22][23]. Hence, for low birth weight infant, might be a higher dose of vitamin D supplement was effectible for vitamin D deficiency prevention, and further studies were needed to explore.…”
Section: Discussionmentioning
confidence: 99%